Multimorbidity, guideline‐directed medical therapies, and associated outcomes among hospitalized heart failure patients. (13th May 2022) - Takeuchi, Shinsuke; Kohno, Takashi; Goda, Ayumi; Shiraishi, Yasuyuki; Kawana, Masataka; Saji, Mike; Nagatomo, Yuji; Nishihata, Yosuke; Takei, Makoto; Nakano, Shintaro; Soejima, Kyoko; Kohsaka, Shun; et al.
Abstract: Aims: Multimorbidity is common among heart failure (HF) patients and may attenuate guideline‐directed medical therapy (GDMT). Multimorbid patients are under‐represented in clinical trials; therefore, the effect of multimorbidity clustering on the prognosis of HF patients remains unknown. We evaluated the prevalence of multimorbidity clusters among consecutively registered hospitalized HF patients and assessed whether GDMT attenuated outcomes. Methods and results: We examined 1924 hospitalized HF patients with reduced left ventricular ejection fraction (<50%) in a multicentre registry (West Tokyo HF Registry: WET‐HF). Ten comorbid conditions in the WET‐HF were abstracted: coronary artery disease, atrial fibrillation, stroke, anaemia, chronic obstructive pulmonary disease, renal dysfunction, obesity, hypertension, dyslipidaemia, and diabetes. Patients were divided into three groups (0–2: n  = 451; 3–4: n  = 787; and ≥5: n  = 686) based on the number of comorbid conditions. The primary composite endpoint was all‐cause mortality and HF rehospitalization. The most prevalent comorbidities were renal dysfunction (67.9%), hypertension (66.0%), and anaemia (53.8%). Increased comorbidity was associated with increased adverse outcomes [3–4: hazard ratio (HR) 1.42, 95% confidence interval (CI) 1.13–1.77, P  = 0.003; ≥5: HR 2.12, 95%CI 1.69–2.65, P  < 0.001; and reference: 0–2] and lower GDMT prescription rate (0–2: 69.2%; 3–4: 57.7%; and ≥5: 57.6%). GDMT was associated with decreased adverse outcomes; this association was maintained even as the comorbidity burden increased but tended to weaken (0–2: HR 0.53, 95%CI 0.35–0.78; P  = 0.001; 3–4: HR 0.82, 95%CI 0.65–1.04, P  = 0.095; and ≥5: HR 0.81, 95%CI 0.65–1.00, P  = 0.053; P for interaction = 0.156). Conclusions: Comorbidity clusters were prevalent and associated with poorer outcomes. GDMT remained beneficial regardless of the comorbidity burden but tended to weaken with increasing comorbidity burden. Further research is required to optimize medical care in these patients.